2008
DOI: 10.1111/j.1440-1754.2007.01268.x
|View full text |Cite
|
Sign up to set email alerts
|

Opportunistic immunisation of infants admitted to hospital: Are we doing enough?

Abstract: Admission to hospital provides opportunities for both routine and catch-up immunisation; however, for opportunistic immunisation to be effective, health service screening and immunisation documentation must be accurate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 7 publications
2
30
0
Order By: Relevance
“…As highlighted by Ressler et al in this edition of the Journal, unfortunately in hospitals many of these opportunities are 'missed'. 3 Missed opportunities to vaccinate can be defined as when 'a child is identified as being eligible for vaccination during the visit, with no contraindication for vaccination, but failed to receive the needed dose(s)'. 4 Ressler et al also noted that the critical first step of identifying that catch-up vaccinations are required is often not occurring.…”
mentioning
confidence: 99%
“…As highlighted by Ressler et al in this edition of the Journal, unfortunately in hospitals many of these opportunities are 'missed'. 3 Missed opportunities to vaccinate can be defined as when 'a child is identified as being eligible for vaccination during the visit, with no contraindication for vaccination, but failed to receive the needed dose(s)'. 4 Ressler et al also noted that the critical first step of identifying that catch-up vaccinations are required is often not occurring.…”
mentioning
confidence: 99%
“…The burden of meeting these targets has traditionally been left with professionals in a primary care role. Although some countries have demonstrated reasonable success with delivering immunisations in this setting, studies have put forward the potential of OI in a secondary care environment 5–9,16,17 …”
Section: Discussionmentioning
confidence: 99%
“…The NIR can be accessed to verify, update or correct the details of the immunisation history, and in our programme allows identification of delayed immunisation from first contact with secondary care. This method of retrieval from a national database is the gold standard 16 and is far more accurate than relying on history taking alone 17 …”
Section: Discussionmentioning
confidence: 99%
“…1 The low rates of documentation in the ED are in stark contrast to a study that found that 98% of patients admitted to an Australian inpatient paediatric unit had their immunisation status recorded. 2 The most frequent recorded parameters were weight and immunisation status. There are two possible reasons for this: firstly, paediatric medication doses and intravenous fluid infusion rates are calculated on weight; and secondly, in our hospital, these were the only parameters with specific documentation areas on the paediatric observation chart.…”
Section: Dear Editor Paediatric Assessment In a General Metropolitanmentioning
confidence: 99%